Análise de diferentes métodos de preenchimento de falhas nos fluxos de CO2: estimativas sobre o arroz irrigado - Diaz, Marcelo Bortoluzzi (2014)
The net exchange of CO2 between the atmosphere and the ecosystem (NEE), represent the balance of the ecosystem respiration (Reco) and gross primary production (GPP), which are directly related to temperature and photosynthetic active radiation (PAR) respectively. Studies related to the exchange of CO2 between ecosystems and atmosphere has been conducted in different ecosystems, with the objective of finding the contribution of different ecosystems to the atmospheric CO2. For this it is important to have a continuous data series. However, these series may fail causing gaps in time series data. Here, were studied gapfilling techniques( multiple linear regression , nonlinear regressions , Look-up Tables, Mean diurnal variation and Neural networks) and the technique of non-linear regressions excel the other, it is indicated to fill the gaps when available variables weather temperature and radiation, not available when these forcings , advise the use of Mean Diurnal variation . Three years of CO2 fluxes over irrigated rice were used to compare the techniques: two years at the Cachoeira do Sul site and one year at Paraiso do Sul site, both located at Rio Grande do Sul. As a result of gapfilling by nonlinear regression, NEE was estimated to be -92 ± 80gC / m² (2010/2011) and 429 ± 188gC / m² (2011/2012), for Cachoeira do Sul and -43 ± 72gC / m² (2003/2004), for Paraíso do Sul.